Muhammad Abdul Wahhab and the influence of Salafiyyah: A study of the movement's influence in Terengganu, Malaysia - Nor Hafizi, Yusof; Tasnim, Abdul Rahman; Fatimah Zaharah, Ismail; Abdillah Hisham, Ab. Wahab; Ahmad Fauzi, Hassan; Mohd A' Tarahim, Mohd Razali (2017)
The debate on Salafiyyah has been ongoing since the early 20th century during the reform (Islah) movement in Egypt and its neighbouring countries. The movement affected local Muslim scholars who had been studying abroad, especially in Saudi Arabia and Egypt, who brought is influence back to their homeland. The objective of this study is to describe the background of the Salafiyyah that spread to Malaysia, especially Terengganu. It also aims to examine the views of several Muslim scholars in Terengganu on the matter. This descriptive study combines both literature review and field study. For the literature review, references such as books, theses, journal articles and paper work were consulted. Interview sessions with the selected scholars were conducted using a structured questionnaire. The findings show that this movement spread in Malaysia from the Islah movement in the Middle East countries and the influence of Malaysian students who studied in Makkah, Egypt and India and brought back these new ideas to Malaysia